Comportamiento bajo compresión uniaxial en micro-retículas polimericas (2017)
The behavior of the rubber-type polymeric micro-gratings under uni-axial loads is studied from three approaches: analytical, computational and experimental. Based on work done on deformation canisters in quasi-static conditions, an analytical model capable of predicting the buckling of the elements of the structure is performed. The simulations are carried out in the software MARC MSCÃ with the appropriate boundary conditions, it must be considered that it is only part of the structure due to the limitations of the software. All the experimental results are presented, from the characterization of the mechanical properties of the base material of the micro-reticles, to the tests of compression of the cellular material. The experimental results are compared with the results obtained from the simulation and the analytical analysis.--Tomado del Formato de Documento de Grado.